Effect of HIV on mortality among hospitalised patients in South Africa - Dirk J. Lamprecht; Neil Martinson; Ebrahim Variava (Southern African Journal of HIV Medicine, 2023)
Background: HIV and AIDS continues to impose substantial healthcare challenges in sub-Saharan Africa, but there are limited local data comparing inpatient outcomes between people with HIV (PLWH) and those uninfected.